UBE2G2 inhibits vasculogenic mimicry and metastasis of uveal melanoma by promoting ubiquitination of LGALS3BP - Andi Zhao; Chenyu Zhou; Jinjing Li; Zijin Wang; Hui Zhu; Shiya Shen; Qing Shao; Qi Gong; Hu Liu; Xuejuan Chen (Acta Pharmaceutica Sinica B)
Uveal melanoma (UM) poses a significant lethality, with approximately 50% of those developing metastases surviving less than one year. In the progression of UM, vasculogenic mimicry (VM) induced by hypoxia plays a pivotal role, which also partially explains the resistance of UM to anti-angiogenic therapies. Nevertheless, the crucial molecular mechanisms underlying VM in the progression of UM remain unclear. We identified ubiquitin conjugating enzyme E2 G2 (UBE2G2) as a critical suppressor through transcriptomic sequencing and metastasis correlation screening. In UM, hypoxia-induced VM and metastasis are markedly exacerbated by UBE2G2 knockdown and significantly alleviated by its overexpression. Mechanistically, UBE2G2 directly binds to galectin 3 binding protein (LGALS3BP) and forms a complex with the E3 ubiquitin ligase tripartite motif containing 38 (TRIM38), facilitating ubiquitination-mediated degradation of LGALS3BP at the K104 residue. Furthermore, UBE2G2 inhibits oncogenic phenotypes by inactivating intracellular PI3K/AKT signaling and reprogramming the tumor microenvironment. Therefore, targeting intercellular and intracellular molecular mechanisms of the hypoxia–UBE2G2–LGALS3BP axis may contribute to developing various therapeutic strategies for UM.